Textbook design of integrated science subject with integrated model in bio magnetic topic - Fitriani, H; Djamas, D; Fauzi, A (Journal of physics. Conference series, 2019)
Textbooks is a student medium to gain the information about the lessons in school. One of the goals of textbooks based on the 2013 curriculum can be used to grow student's curiosity and develop their skills. In Science Lesson, the textbook has an alignment of topics for physics, biology, and chemistry subjects. Based on observation and needs analysis results textbook have not reached the standard of student needs. Science textbooks are still fragmented and the content is incomplete. In this research, the design of science textbook was made to make students' interest in learning and have a connected theme of each material. The integrated model was developed in bio magnetic topic. This model was linked for each basic competency material that related with chosen topic. The results of the design obtained a student worksheet form that can describe every event of subjects, in addition there are steps of science integrated learning in teaching and learning process. There were three subthemes produced, i.e. bio magnetic in the body, bio magnetic in blood circulation and bio magnetic measurement.